AN ANALYSIS OF CODE SWITCHING USED IN YOUTUBE PODCAST OF DEDDY CORBUZIER ENTITLED THE ART OF BEING POOR EPISODE - Alessandri, Sandro; Syarfi, M.; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
bstract: Code-switching is a term in linguistics referring to using more than onelanguage or variety in conversation. Code-switching occurs when a speaker alternates between two or more language (bilingualism/multilingualism) or language varieties. The phenomenon of code-switching in Indonesia nowadays is quite easy to find and use by many people, especially in the South Jakarta, as they called the people who use code switching as “Anak Jaksel”. This study analyzes the types and reason of code switching that occurs in a YouTube Podcast of Deddy Corbuzier entitled The Art of Being Poor episode. The research is using a qualitative method, the researcher collecting the data through the utterances of host and source person in the video. The total of 94 data from the whole 69 minutes duration of the video is showing Intra-sentential type is the most showing type, representing 55 times (59%) of the total number of code switching occurences. While the most showing type is Talking about particular topic, representing 42 times (45%) of the total number of code switching occurences. These finding is imperative for educators to comprehend the functions and motivations behind code switching. When being use appropriately, code switching can serve as a valuable tool to enhance student learning and facilitate more effective teaching practices. By broadening their understanding of code switching, students can enrich their knowledge of English and enhance their communication skills.Key Words: Analysis, Code-switching, YouTube Podcast.